Responsibility at work: how leading professionals act (or don't act) responsibly - Gardner, Howard (Jossey-Bass/Wiley, 2007)
Taking ultimate responsibility / William Damon and Kendall Bronk -- The ability to respond / Susan Verducci -- Creativity and responsibility / Mihaly Csikszentmihalyi and Jeanne Nakamura -- A call to serve : an exploration of humane creators / Wendy Fischman -- A balancing act : how physicians and teachers manage time pressures and responsibility / Jeffrey Solomon -- Placing God before me : spirituality and responsibility at work / Seth Wax -- Responsibility and leadership / Andreas Schrer -- Service at work / Lynn Barendsen -- Beyond the gender stereotype : responsibilities to self and others / Carrie James -- Control and responsibility : a Danish perspective on leadership / Hans Henrik Knoop -- Constraining responsibility : choices and compromises / Laura Horn and Howard Gardner -- Irresponsible work / Howard Gardner -- Practicing responsibility / Jeanne Nakamura -- The goodwork toolkit : from theory to practice / Lynn Barendsen and Wendy Fischman
Includes bibliographical references and index
Keywords: Verantwortung; Führungskraft; Betriebspsychologie; Arbeitspsychologie